2020
DOI: 10.1021/acsomega.0c03164
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin-Based Electrospun Fibers Insolubilized by Horseradish Peroxidase-Catalyzed Cross-Linking for Biomedical Applications

Abstract: Gelatin-based water-insoluble nanofibers with a diameter of 160 nm were obtained from electrospinning aqueous solutions containing gelatin with phenolic hydroxyl (Ph) moieties (Gelatin-Ph) and horseradish peroxidase (HRP). The water insolubility of the nanofibers was accomplished through HRP-catalyzed cross-linking of the Ph moieties by exposing the electrospun nanofibers to air containing hydrogen peroxide. The HRP activity in the electrospun nanofibers was 65% that of native HRP. The cytocompatibility necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…The H 2 O 2 molecules from saturated air could be mildly diffused into fibrous structure and provide uniform crosslinking without specific concerns for shape deformation and liquefaction of electrospun fibers before proceeding of covalent crosslinking of Ph moieties to each other and stable solidification of fibers. 28 The usefulness of HRP-catalyzed crosslinking of polymers with Ph moieties (polymer-Ph) in an aqueous solution for obtaining stable 3D construct in bulk gels is well recognized. 26,29,30 Polymers possessing Ph moieties enzymatically crosslinked and hydrogelated in presence of HRP& H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The H 2 O 2 molecules from saturated air could be mildly diffused into fibrous structure and provide uniform crosslinking without specific concerns for shape deformation and liquefaction of electrospun fibers before proceeding of covalent crosslinking of Ph moieties to each other and stable solidification of fibers. 28 The usefulness of HRP-catalyzed crosslinking of polymers with Ph moieties (polymer-Ph) in an aqueous solution for obtaining stable 3D construct in bulk gels is well recognized. 26,29,30 Polymers possessing Ph moieties enzymatically crosslinked and hydrogelated in presence of HRP& H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The covalent crosslinking using chemicals such as glutaraldehyde and carbodiimide crosslinking are not safe, and the rate of crosslinking is too low [9,11,21,44]. Recently, Sakai et al reported the feasibility of brous mat fabrication through HRP-mediated crosslinking for GelaPh within minutes, that proved viability of corresponding approach for other biopolymer development and application for biomedical elds [31]. Therefore, here we have attempted to synthesize Ph conjugated PVA and Gela as an electrospinning media and then crosslinked their molecules through HRP-mediated crosslinking using vaporized H 2 O 2 as an electron donor.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, addition of GelaPh in higher concentration improved tensile strength in lower degree due to reduction of PVAPh crosslinking and correspondingly higher GelaPh crosslinking in the hydrogel structure since Gela inherently possessed a weak mechanical strength [11,23,31]. The PVAPh brous mat extended without breaking up to 183% strain, which was highest among brous mats (Fig.…”
Section: Mechanical Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…34 Among the wide range of crosslinking enzymes, Horseradish peroxidase (HRP) has been widely used to catalyze polymers with phenolic hydroxyl (Ph) moieties using hydrogen peroxide (H 2 O 2 ) as an oxidant under mild conditions. 3538 The advantages of using HRP for biological applications include fast gelation rate, having moderate substrate specificity, manageable gelation rate, and crosslinking density. 3941 Besides carbodiimide activation chemistry which is used for alginate phenolation has been shown to have a variety of advantages, such as enhancement of osteo-compatibility, 42 cellular attachment, 43 and muco-adhesiveness.…”
Section: Introductionmentioning
confidence: 99%